Clinical application of regional citrate anticoagulation for continuous renal replacement therapy in children with liver injury - Hu, Fang; Sun, Yuelin; Bai, Ke; Liu, Chengjun (Frontiers in Pediatrics, 2022)
Background: Regional citrate anticoagulation (RCA) is increasingly used for continuous renal replacement therapy (CRRT) in children, but rarely used in those children with liver failure. We analysis this issue through the following research. Methods: We retrospectively analysed 75 children with liver injury who underwent RCA-CRRT in the Pediatric Intensive Care Unit (PICU) of Children's Hospital of Chongqing Medical University. The patients were divided into Group A (liver failure group) and Group B (liver dysfunction group). The two groups were compared in terms of the incidence of bleeding, clotting, citrate accumulation(CA), acid-base imbalance and electrolyte disturbance, as well as filter lifespan, changes in biochemical indicatorst, and CRRT parameter adjustment, etc., to evaluate the clinical safety and efficacy of RCA-CRRT in children with liver injury, and to explore RCA-CRRT management strategies. Results: The total incidence of CA and persistent CA in Group A were significantly higher than those in Group B (40.5% vs 15.2%, 8.8% vs 1.4%); and the CA incidence was significantly reduced after adjustment both in Group A and Group B. The blood pump speed and citrate pump speed after adjustment were lower than the initial setting values both in Group A and Group B, and the dialysis speed plus replacement speed were higher than the initial settings parameters. Conclusion: For children undergoing RCA-CRRT, the risk of CA is significantly higher in children with liver failure than those with liver dysfunction, but through proper adjustment of the protocol, RCA-CRRT can still be safely and effectively approached for children with liver dysfunction and even liver failure.